Biological Resources of the Northern USSR (Biologicheskie Resursy Sushi Krainego Severa). - COLD REGIONS RESEARCH AND ENGINEERING LAB HANOVER NH (1974)
The Presidium of the USSR Academy of Sciences has examined the main problems of the investigation of the biological resources of the dry land of the Russian Far North. The biosphere of polar regions is constantly under the influence of two factors: the low air temperature and the negative temperatures of the cryosphere - the permafrost. This dual press of the cold explains the low unstable productivity and slight functional activity of biogeocenoses of the Far North and at the same time development of special species of plants and animals adapted to the extreme conditions, as well as the presence of the unique forms in which they coexist with each other and the environment -- tundra biogeocenoses. Draft trans. of Akademiya Nauk SSSR. Vestnik, n9 p5-9 1972.